Global organization of innovation processes - Ben Mahmoud-Jouini, Sihem; Burger-Helmchen, Thierry; Charue-Duboc, Florence; Doz, Yves (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
In this article, we first present a brief overview of the historical evolution of global innovation in multinational firms. We then outline four components and challenges facing firms that are evolving towards global innovation. Next, we focus on the beginning and end phases of the innovation process: their inception and their diffusion. We show that the stakes related to inception tend to sustain internationalization but induce ever more complex innovation diffusion. In the conclusion, we present open issues and questions that merit further attention and research by the academic community working at the intersection of innovation management and international management.